Comparative study of radiation tolerance of GaN and Ga2O3 polymorphs. (June 2022) - Titov, A.I.; Karabeshkin, K.V.; Struchkov, A.I.; Nikolaev, V.I.; Azarov, A.; Gogova, D.S.; Karaseov, P.A.
Abstract: The mechanisms of ion-induced defect formation and physical characteristics promoting radiation tolerance of wide and ultra-wide bandgap semiconductors are not well-studied and understood. In contrast to gallium nitride (GaN), gallium oxide (Ga2 O3 ) can be crystallized in several polymorphs having different crystal structures and physical properties. In the preset paper, the damage buildup in wurtzite GaN as well as in corundum ( α -) and monoclinic ( β -) Ga2 O3 polymorphs bombarded at room temperature with 40 keV P + ions is studied by Rutherford backscattering/channeling spectrometry. We demonstrate that ion-beam-induced damage formation in Ga2 O3 is different from that observed in GaN and dramatically depends on the polymorph type. Both Ga2 O3 polymorphs cannot be rendered amorphous and exhibit considerably higher damage saturation at ∼90% of the full amorphization as compared to that of GaN. Intriguing enough the metastable α -Ga2 O3 demonstrates considerably higher radiation resistance as compared to the most thermodynamically stable β -Ga2 O3 polymorph. Furthermore, our results indicate that the sample surface and dynamic annealing play a significant role in the ion-induced damage formation processes in all Ga-based compounds studied. Highlights: Kinetics of ion irradiation damage accumulation in α- and β-Ga2 O3 and GaN is studied. α -Ga2 O3 is more susceptible to radiation damage than GaN. α -Ga2 O3 is considerably higher radiation resistant then the stable β -Ga2 O3 . Mechanisms of radiation damage formation in the α - and β -Ga2 O3 are different.